Ulcerative Colitis Database: An Integrated Database and Toolkit for Gene Function and Medication Involved in Ulcerative Colitis. Issue 8 (August 2015) - Shen, Jun; Mao, Ai-Ping; Zhu, Ming Ming; Zhao, Pei; Xu, Jun Jie; Zuo, Zhixiang
Abstract : Background: Over the last decade, a massive amount of well-annotated genomic data has been accumulated on the pathogenesis and therapies for ulcerative colitis (UC). However, a comprehensive repository is not available yet. Methods: Ulcerative Colitis Database (UCDB) was constructed using text mining followed by manually curating on the literature to collect the reliable information of UC-related genes, drugs, and susceptibility loci. UC DNA microarray data were collected. R packages were used to implement gene expression analysis toolkit. Results: UCDB includes 4 separate but closely related components: "UC GENE, " "UC DRUG, " "UC LOCUS, " and "UC ANALYSIS." The UC GENE contains comprehensive information for 1151 UC-related genes manually curated from 2919 publications. The UC DRUG includes information for 248 drugs manually curated from 2344 publications. "UC LOCUS" includes 110 UC susceptibility SNP loci, which were collected from 12 Genome-Wide Association Studies. A comprehensive expression quantitative trait loci browser was also implemented. The UC ANALYSIS is an expression analysis toolkit for 37 UC expression array data sets, which contains 1098 samples. The toolkit can be used to do gene expression correlation, clustering, differentially expressed, and Gene Set Enrichment Analysis (GSEA). Conclusions: UCDB provides a comprehensive collection of well-curated UC-related genes and drugs, and straightforward interfaces for gene expression analyses. UCDB is a useful leading resource for both basic and clinical research and will benefit UC community worldwide. UCDB is freely accessible athttp://seiwertlab.uchicago.edu/UCDB . Abstract : Article first published online 29 April 2015.